2016
DOI: 10.1111/wrr.12450
|View full text |Cite
|
Sign up to set email alerts
|

Imaging mass spectrometry for accessing molecular changes during burn wound healing

Abstract: The spatiotemporal analysis of the proteomic profile during human wound healing is a critical investigative step that can establish the complex interplay of molecular events that comprise the local response to burn injury. Partial-thickness wound samples with adjacent "normal" skin were collected from twenty-one patients with burn wounds and examined across a time spectrum ranging from the acute injury period at 3, 6, 11 days to the later hypertrophic scar period at 7 and 15 months. The techniques used for his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…from the acute period (days after trauma) to the later hypertrophic scar (months after trauma). 239 This histology-directed tissue analysis found that the expression of several inflammatory proteins was correlated to the wound healing process, which could be used to predict whether human burn victims are at risk of disfiguring hypertrophic scar formation.…”
Section: Msi In Non-cancer Clinical Researchmentioning
confidence: 99%
“…from the acute period (days after trauma) to the later hypertrophic scar (months after trauma). 239 This histology-directed tissue analysis found that the expression of several inflammatory proteins was correlated to the wound healing process, which could be used to predict whether human burn victims are at risk of disfiguring hypertrophic scar formation.…”
Section: Msi In Non-cancer Clinical Researchmentioning
confidence: 99%
“…Hart et al [59] utilised MALD-MSI for the study of ex vivo human skin in a search for biomarkers of skin sensitization and protocols for the preparation of skin for imaging have been published [65][66][67]. Wound healing has been the subject of a number of MSI publications [35,38,68,54,69]. Taking as illustrative of these the 2016 study of burn wounds by Taverna et al [54] the methodology used can be summarised as Table 7 shows and it is a typical methodology for intact protein imaging in skin.…”
Section: Applicationmentioning
confidence: 99%
“…Wound healing has been the subject of a number of MSI publications [35,38,68,54,69]. Taking as illustrative of these the 2016 study of burn wounds by Taverna et al [54] the methodology used can be summarised as Table 7 shows and it is a typical methodology for intact protein imaging in skin.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens were collected from the tumor and processed, as previously described. [33][34][35] Briefly, samples were wrapped in aluminum foil, snap-frozen in liquid nitrogen, and then stored at 280 o C.…”
Section: Collection Of Tumor Specimens For Mass Spectrometry Imagingmentioning
confidence: 99%